2007
DOI: 10.1097/meg.0b013e3280102f5e
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid allows effective selection of areas for obtaining biopsy samples in Barrett??s esophagus

Abstract: This prospective study shows that acetic acid test is useful for standard, nonmagnifying, endoscopic detection of dysplasia and cancer in Barrett's esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…The per-patient sensitivity and specificity of new imaging techniques have ranged from 33% to 100% and 56% to 100%, respectively. 7,9,14,[16][17][18]21,24,[30][31][32][33][34][35] Finally, the primary costs associated with surveillance include physician time, nursing time, facility utilization (procedure rooms, time, and equipment for patient scheduling, reminders, and patient preparation), sedation expenses, equipment outlays (endoscopes, biopsy forceps, imaging devices), pathology processing, pathologist charges, time lost from work for the patient, and time lost from work for persons accompanying the patient. Adoption of imaging could conceivably affect all of these except the last 2 (time lost from work).…”
Section: Literature Review Summarymentioning
confidence: 99%
“…The per-patient sensitivity and specificity of new imaging techniques have ranged from 33% to 100% and 56% to 100%, respectively. 7,9,14,[16][17][18]21,24,[30][31][32][33][34][35] Finally, the primary costs associated with surveillance include physician time, nursing time, facility utilization (procedure rooms, time, and equipment for patient scheduling, reminders, and patient preparation), sedation expenses, equipment outlays (endoscopes, biopsy forceps, imaging devices), pathology processing, pathologist charges, time lost from work for the patient, and time lost from work for persons accompanying the patient. Adoption of imaging could conceivably affect all of these except the last 2 (time lost from work).…”
Section: Literature Review Summarymentioning
confidence: 99%
“…Enhanced magnification with acetic acid application to the mucosa seems promising,61 and a classification of the mucosal pit pattern of BO based on the use of this method has also been introduced 62. However, data on this technique remain limited 6365…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…While no randomised controlled trials for its use in the oesophagus exist, cohort studies have demonstrated effectiveness in the identification of dysplasia. The sensitivity for the identification of neoplasia has been suggested to be 71-100%, with a specificity between 80 and 99% (Vázquez-Iglesias et al 2007;Gossner et al 2005;Fortun et al 2006;Longcroft-Wheaton et al 2010). We believe that this is the dye of the future in the evaluation of Barrett's.…”
Section: Oesophageal Cancermentioning
confidence: 77%